Allocating Lower Duwamish Waterway Sediment Remediation Cost by Insurance Policy Period. Issue 1 (17th September 2020) - Sullivan, Daniel G.
Abstract: To mitigate risk from contaminated sediment in the Lower Duwamish Waterway, the United States Environmental Protection Agency selected a remedial strategy that will address impacted shallow sediment. Since new sediment is deposited in the waterway each year, remediation of shallow sediment primarily addresses new sediment in many areas, and remediation costs can be time-allocated accordingly. For example, by selecting 1986 as the key year, it can be shown that much of the environmental injury being remediated occurred after the Absolute Pollution Exclusion was incorporated into most General Liability insurance policies. This methodology could be applied to other mega-sediment remediation sites. The author notes, however, that this analysis method may not be directly applicable to allocating CERCLA liability due to the differing emphasis placed on the timing of environmental injury.